Transcriptome Analysis Reveals the Important Role of WRKY28 in Fusarium oxysporum Resistance - Diao, Jian; Wang, Jiaqi; Zhang, Ping; Hao, Xin; Wang, Yang; Liang, Liwei; Zhang, Yue; Ma, Wei; Ma, Ling (Frontiers in Plant Science, 2021)
Root rot of Populus davidiana × P. alba var. pyramidalis Louche (Pdpap) is caused by Fusarium oxysporum. We used RNA sequencing to study the molecular mechanisms and response pattern of Pdpap infected by F. oxysporum CFCC86068. We cloned the PdpapWRKY28 transcription factor gene and transformed the recombinant vector pBI121-PdpapWRKY28 into Pdpap. The resistance function of PdpapWRKY28 was verified using physiological and biochemical methods. By means of RNA sequencing, we detected 1,403 differentially expressed genes (DEGs) that are common in the different treatments by F. oxysporum. Furthermore, we found that overexpression of the PdpapWRKY28 gene may significantly improve the resistance of Pdpap plants to F. oxysporum. Our research reveals a key role for PdpapWRKY28 in the resistance response of Pdpap to F. oxysporum. Additionally, our results provide a theoretical basis for in-depth research on resistance breeding to combat root rot.